Coupled otolith and foraminifera oxygen and carbon stable isotopes evidence paleoceanographic changes and fish metabolic responses - K. Agiadi; I. Vasiliev; G. Butiseacă; G. Kontakiotis; D. Thivaiou; E. Besiou; S. Zarkogiannis; E. Koskeridou; A. Antonarakou; A. Mulch; A. Mulch (Biogeosciences, 2024)
Capturing the mechanisms leading to the local extirpation of a species in deep time is a challenge. Here, by combining stable oxygen and carbon isotopic analyses on benthic and planktonic foraminifera and the otoliths of pelagic and benthic fish species, we reveal the paleoceanographic regime shifts that took place in the eastern Mediterranean from 7.2 to 6.5 Ma, in the precursor phase to the Messinian salinity crisis, and discuss the fish response to these events. The stepwise restriction of the Mediterranean–Atlantic gateway impacted the metabolism of fishes in the Mediterranean, particularly those dwelling in the lower, deeper part of the water column. An important shift in the Mediterranean paleoceanographic conditions took place between 6.951 and 6.882 Ma, from predominantly temperature to salinity control, which was probably related to stratification of the water column. A regime shift at 6.814 Ma, due to changes in the influx, source and/or preservation of organic matter, led to pelagic–benthic decoupling of the fish fauna. At that time, the oxygen isotopic composition of benthic fish otoliths reflects higher salinity in the lower part of the water column that is accompanied by a rapid fluctuation in the carbon isotopic composition (a proxy for the metabolic rate), ultimately leading to the local extirpation of the benthic species. Overall, our results confirm that otolith stable oxygen and carbon isotope ratios are reliable proxies for paleoceanographic studies and, when combined with those of foraminifera, can reveal life history changes and migration patterns of teleost fishes in deep time.